High-Dose Phenobarbital for Ohtahara Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Oral high-dose phenobarbital therapy was effective in the control of tonic spasms in a 1 month-old-infant with early infantile epileptic encephalopathy with suppression bursts (Ohtahara syndrome) treated at Tokyo Metropolitan Hachioji Children's Hospital, Tokyo, Japan.